The Influence of Motivation on Students’ Achievement in Learning Arabic - Muhamad Hasyim; Lidia Syafitri Arum; Muh. Muhayyan Shodiki; Rohatun; Sahroni; L. Muh. Hendriawan Saufiyandi; M. Habib Alawi; Nuri Handayani; Nirmala Ramdani (Formad English Foundation NTB Jakarta, 2026)
Motivation has been widely recognized as a critical factor influencing students’ academic achievement, particularly in foreign language learning contexts such as Arabic. However, existing studies often examine motivation in fragmented ways, without providing a comprehensive understanding of its multidimensional nature and its interaction with learning processes. Therefore, this study aims to systematically review and synthesize the influence of motivation on students’ achievement in learning Arabic, with a focus on intrinsic motivation, extrinsic motivation, and self-efficacy. This research employed a qualitative systematic literature review design, analyzing peer-reviewed journal articles and scholarly publications published between 2015 and 2025. Data were collected through a documentation technique and analyzed using qualitative content analysis to identify recurring themes, patterns, and relationships among variables. The findings reveal that motivation has a significant and positive relationship with students’ academic achievement in Arabic learning. Intrinsic motivation and self-efficacy emerged as the most influential dimensions, while extrinsic motivation played a supportive role in enhancing engagement. Furthermore, the study found that motivation interacts dynamically with instructional strategies and educational contexts, shaping students’ learning processes and outcomes. In conclusion, motivation is a central and integrative factor that determines students’ success in learning Arabic. The study highlights the importance of fostering intrinsic motivation and strengthening self-efficacy through innovative and supportive learning environments. These findings contribute to both theoretical understanding and practical improvement of Arabic language education.